Profil Komunikasi Matematika Tulis Peserta Didik SMP dalam Menyelesaikan Soal AKM Subdomain Geometri - Wulanningrum, Annisa Maulidha; Ekawati, Rooselyna (MATHEdunesa, 2025)
This study aims to describe written mathematics communication of male and female junior high school students with high mathematics ability in solving AKM problems in the geometry subdomain. The research subjects were a male students and a female students in grade 8 with equal high mathematics ability. This research is limited to AKM problems in the geometry subdomain of shapes material with cognitive level of reasoning, personal context, and description questions. Data collection was used with a test of mathematical ability (TKM), a test of solving AKM, and interviews. The results of TKM were used to determine the research subject. The results of solving AKM problems in the geometry subdomain were analyzed by paying attention to the indicators of written mathematical communication. The results of interview were analyzed by data reduction, data presentation, and conclusion drawing stages. The results of written mathematical communication research show that  male students can state information that has a value without represent it using symbols; draw a flat shape according to the information in the problem; connect ideas by writing the value on the picture caption; interpret ideas by writing the appropriate formula; check steps that do not have complicated calculations; and female students state information by writing it completely without representing it with symbols; describe flat buildings according to the information in the problem; connect ideas by writing symbols as a description of the picture; interpret ideas by writing the appropriate formula; evaluate the results work by re-examining steps that without calculation process